Truncated Hantavirus Nucleocapsid Proteins for Serotyping Hantaan, Seoul, and Dobrava Hantavirus Infections - Araki, Koichi (American Society for Microbiology, 2001)
Truncated recombinant nucleocapsid proteins (rNPs) of Hantaan virus (HTNV), Seoul virus (SEOV), and Dobrava virus (DOBV) were expressed by a baculovirus system. The truncated rNPs, which lacked 49 (rNP50) or 154 (rNP155) N-terminal amino acids of the NPs of HTNV, SEOV, and DOBV, were able to differentiate HTNV-, SEOV-, and DOBV-specific immune sera. Recombinant NP50s retained higher reactivities than rNP155s and were proven useful for enzyme-linked immunosorbent assay (ELISA). The ELISAs based on the rNP50s of HTNV, SEOV, and DOBV successfully differentiated three groups of patient sera, previously defined by neutralization tests: 17 with HTNV infection, 12 with SEOV infection, and 20 with DOBV infection. The entire rNP of Puumala virus (PUUV) distinguished PUUV infection from the other types of hantavirus infection. Serotyping with these rNP50s can be recommended as a rapid and efficient system for hantavirus diagnosis.